Palmer Amaranth Populations from Kansas with Multiple Resistance to Glyphosate, Chlorsulfuron, Mesotrione, and Atrazine - V. Kumar; P. W. Stahlman; G. Boyer (Kansas Agricultural Experiment Station Research Reports, 2018)
Multiple herbicide-resistant (MHR) Palmer amaranth poses a serious management concern for growers across the United States. Since 2014, several Palmer amaranth populations with suspected resistance to most commonly used herbicides were collected in random field surveys across Kansas. This study aimed to characterize the resistance levels to glyphosate (EPSPS inhibitor), mesotrione (HPPD inhibitor), chlorsulfuron (ALS inhibitor), and atrazine (PS II inhibitor) in three suspected MHR Palmer amaranth populations (KW2, PR8, and BT12) compared to a known herbicide-susceptible (SUS) population. Dose-response studies revealed that PR8 and BT12 populations had 7- to 14-fold level resistance to glyphosate, and up to 12-fold level of resistance to chlorsulfuron (Glean herbicide) on the basis of visible control (LD50values) and shoot dry weight response (GR50values). The KW2, PR8, and BT12 populations also showed 2- to 4-fold resistance to mesotrione (Callisto herbicide) relative to SUS population. Based on plant dry weight response (GR50values), the KW2 and BT12 populations showed 5- and 16-fold resistance to atrazine (AAtrex XP), respectively, compared with the SUS population. These results confirm the first report on the evolution of a Palmer amaranth population (BT12) with multiple resistance to glyphosate (12 to 14 fold), chlorsulfuron (11 fold), mesotrione (2 to 4 fold), and atrazine (16 fold) in Kansas. Further studies are in progress to investigate the response of these MHR populations to fomesafen (PPO inhibitor); 2,4-D; and dicamba (synthetic auxins) herbicides.
Keywords: Evolution; Palmer amaranth; AAtrex®; Callisto®; Glean®; Roundup® PowerMax; multiple herbicide resistance